A Review Of Concentrating Solar Power (Csp) In Malaysia Environment - Affandi, Rosnani; Ab Ghani, Mohd Ruddin; Gan, Chin Kim; Jano, Zanariah (Blue Eyes Intelligence Engineering & Sciences Publication Pvt. Ltd., 2013)
Malaysia has an abundance of solar energy. While the magnitude for average daily solar irradiations in Malaysia is around 4.21–5.56 kWhm−2, the sunshine duration is more than 2,200 hours per year. However, the focus on solar energy in Malaysia is mainly on the Photovoltaic (PV) panel to generate electricity. There is still lack of thorough investigation in implementing the solar thermal, such as the Concentrating Solar Power (CSP) in Malaysian environment. This paper reviews the CSP technology and the potential of developing CSP plant in the Malaysian environment by taking into account the Direct Normal Irradiance (DNI) and a few geographical aspects.